2017
DOI: 10.1590/1517-869220172304169935
|View full text |Cite
|
Sign up to set email alerts
|

Regulação Gênica Da via Ampk Pelo Exercício Físico: Revisão Sistemática E Análise in Silico

Abstract: Artigo de revisão sistemáticASyStematic Review aRticle aRtículo de ReviSión SiStemática RESUMOIntrodução: Novos estudos de regulação gênica do exercício físico por meio de técnicas pós-genômicas em ensaios de resistência (endurance) e força caracterizam a transcriptômica do exercício físico. Entre os genes afetados, destacamos a via da proteína quinase ativada por AMP (AMPK), cuja ativação ocorre durante o exercício como resultado das alterações dos níveis de fosfato energético da fibra muscular. Objetivo: Ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In the intervention and control groups, hydrotherapy favored adequate maternal metabolic and cardiovascular adaptation to pregnancy [46]. Among other benefits, physical exercise increases the body's consumption of glucose causing negative regulation of the genes encoded in the MO25 protein and positive regulation of the AMPK encoding genes that activate the transducer of regulatory protein CREB 2 (TORC2) which has the function of controlling protein activities and inhibiting liver conversions of "aglicanos" compounds (pyruvate), reducing gluconeogenesis [47].…”
Section: Obstetric Therapies With Oral Antidiabetic Metformin Hydrochmentioning
confidence: 99%
“…In the intervention and control groups, hydrotherapy favored adequate maternal metabolic and cardiovascular adaptation to pregnancy [46]. Among other benefits, physical exercise increases the body's consumption of glucose causing negative regulation of the genes encoded in the MO25 protein and positive regulation of the AMPK encoding genes that activate the transducer of regulatory protein CREB 2 (TORC2) which has the function of controlling protein activities and inhibiting liver conversions of "aglicanos" compounds (pyruvate), reducing gluconeogenesis [47].…”
Section: Obstetric Therapies With Oral Antidiabetic Metformin Hydrochmentioning
confidence: 99%
“…Physical activity can activate AMPK and reduce conversions of "aglicanos" compounds. 19 A recent study showed that pregnant women who followed the guidelines on physical activities and diet composition altered gene expression that relates to fatty acid transport. Active women had lower expression of fatty acid transport protein 4 (FATP4).…”
Section: Physical Activity and Gene Regulation Programsmentioning
confidence: 99%
“…(mTOR), which regulates energy in the intracellular space. 19 Physical activity activates AMPK in several ways and in different routes. In order to reduce gluconeogenesis, physical exercise increases the consumption of glucose by the organism and, subsequently, there is a negative regulation of the genes encoded in the MO25 protein.…”
Section: Authors' Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conclusion: Acute isometric exercise with a handgrip at 50% of CVM was able to promote a significant reduction in capillary glycemia levels in elderly women with DM2, exposed to the exercise protocol. independentemente da modalidade do exercício 12,13 .…”
Section: Introductionmentioning
confidence: 99%